COVID-19 associated mucormycosis and COVID-19 vaccination status - Godse , Ashwini; Raj Shivalingaiah, Pruthvi; Mujahid, Zaaraasmat Ahesannawaz; Kalyanapura Gurumurthy, Manjula; Elachola, Yumna Beegum; Johnson, Jewel Christy (International Journal of Research in Medical Sciences, 2023)
Background: Mucormycosis is lethal angio invasive fungal infection affecting mainly the immunocompromised individuals. During second wave of COVID-19 pandemic there was rise in number of rhino-orbito-cerebral (ROCM) cases in both COVID-19 affected patients and patients who recovered from COVID-19 infection. This study was conducted to know the anatomical site and extent of involvement in head and neck region in both COVID-19 vaccinated and unvaccinated individuals. Methods: A retrospective descriptive study was conducted between May 2021 and November 2021 at Bowring and lady Curzon hospital, Shri Atal Bihari Vajpayee medical college and research institute, Bangalore, Karnataka, India. 358 patients with post-covid RTPCR negative rhino-orbital mucormycosis were included in the study. The demographic data, COVID-19 vaccination status and anatomical sites of involvement in the patients was collected and analysed. Results: 4 (1.11%) patients were fully vaccinated with 2 doses of covid vaccine, 18 (5.02%) patients were partially vaccinated, 336 (93.85%) were unvaccinated. Majority of the patients were in the age group of 41-60 years in all the groups. In unvaccinated group, majority of the patients presented with stage II/III disease (48.51%; 39.88% respectively) and 39 (11.60%) patients with stage IV ROCM. Conclusions: The extent and severity of ROCM was higher in COVID-19 unvaccinated patients as compared to vaccinated group. Further studies are required to determine the role of COVID-19 vaccine in reducing the severity of the of ROCM.